Excise tax incidence: The inequity of taxing obesity and beauty - Osaid Alshamleh; Glenn P. Jenkins; Tufan Ekici (Queen's University, Department of Economics, 2023)
The estimation and analysis of the distribution of the negative health impacts of certain commodities subject to excise taxes in Belize and the distribution of the burdens of the excise taxes across households of different income levels are the focus of this article. Particular attention is given to the taxation of soft drinks and cosmetics. We examine the income distribution and tax revenue impacts using the commodity data from the household expenditure survey by and the effective tax rates expressed as a percentage of the value of the final consumption of each item. As in many developing countries, taxes on alcoholic beverages and tobacco products are found to be regressive. The most regressive excise taxes are on soft drinks and cosmetics. Households across the economy pay more in excise taxes on cosmetics than they do on either alcoholic beverages or tobacco products. Relative to the level of household expenditures, the burden of the excise taxes on cosmetics is highest for households in the lowest quintile of total expenditures. The impact of soft drinks in creating obesity is likely to be much greater for high income households whose total consumption per household is twice that of low-income households.
Keywords: H22; L66; 330; excise tax; tax incidence; cosmetics; soft drinks; obesity; regressivity; Belize